Analisis Break Even Point Multi Produk sebagai Alat Bantu Perencanaan Laba pada UMKM Tape Uli Mak Can - Gita Lestari; Angga Sanita Putra; Nesti Hapsari; Achmad Nawawi; Madjidainun Rahma (Universitas Persada Indonesia YAI, 2026)
Traditional food micro, small, and medium enterprises (MSMEs) play an important role in Indonesia’s economy; however, many business owners have not yet implemented data-driven profit planning or Break Even Point (BEP) analysis. Tape Uli Mak Can, a traditional Betawi food business located in North Cikarang, Bekasi Regency, has never systematically applied BEP analysis. This study aims to analyze the cost structure, calculate the multi-product BEP based on the sales mix, determine the sales target required to achieve the planned profit, and measure the Margin of Safety (MoS). A quantitative descriptive approach was employed using primary data collected through interviews, observations, and financial documentation over one month. The analysis included cost classification, Contribution Margin Ratio (CMR), Weighted Average Contribution Margin Ratio (WACMR), multi-product BEP, profit planning, and MoS. The results indicate that the total monthly cost was IDR 1,416,111, consisting of 2.83% fixed costs and 97.17% variable costs. The CMR was 14% for Tape and 26% for Uli, resulting in a WACMR of 22%. The overall BEP was achieved at monthly sales of IDR 182,323. To increase profit by 10%, sales need to increase by approximately 9%. An MoS of 90% indicates a very high level of business safety. The multi-product BEP analysis proved to be an effective tool for profit planning and financial decision-making for MSMEs.